2020
DOI: 10.3390/land9090319
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Landforms for Digital Soil Mapping in Urban Areas Using LiDAR Data Derived Terrain Attributes: A Case Study from Berlin, Germany

Abstract: In this study, a knowledge-based fuzzy classification method was used to classify possible soil-landforms in urban areas based on analysis of morphometric parameters (terrain attributes) derived from digital elevation models (DEMs). A case study in the city area of Berlin was used to compare two different resolution DEMs in terms of their potential to find a specific relationship between landforms, soil types and the suitability of these DEMs for soil mapping. Almost all the topographic parameters were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Slope curvature refers to the rate of slope change along the land's surface and contributes actively to flood and wildfire formations (Minár et al 2020). Concave or depressional terrains (negative curvature) can trap water during heavy rainfall, leading to temporary ponding or small-scale flooding in these regions (Mohamed 2020). Concave curvature can accumulate dead plant material, creating a higher fuel load and increasing the hazard of forest fires (Banerjee 2021).…”
Section: (Iv) Slope Curvaturementioning
confidence: 99%
“…Slope curvature refers to the rate of slope change along the land's surface and contributes actively to flood and wildfire formations (Minár et al 2020). Concave or depressional terrains (negative curvature) can trap water during heavy rainfall, leading to temporary ponding or small-scale flooding in these regions (Mohamed 2020). Concave curvature can accumulate dead plant material, creating a higher fuel load and increasing the hazard of forest fires (Banerjee 2021).…”
Section: (Iv) Slope Curvaturementioning
confidence: 99%
“…Due to highresolution technologies, it's possible to enhance the built heritage knowledge and simultaneously monitor the morphological and micro-topographic aspects of the territory. Previous research works also demonstrated the flexibility of a 3D GIS multiscale database, that manages to operate in different built and natural heritage contexts and to monitor the conservation status of vegetation and other natural components of the territorial context, such as water and soil shapes (Mohamed, 2020). In fact, structuring the obtained dataset onto a 3D geospatial database in a GIS environment, where both available geographic datasets and collected data are integrated and continuously updated, allows multiple possibilities not only for data visualisation and archiving, but mainly for geographical data correlation and supporting interpretation.…”
Section: Related Workmentioning
confidence: 99%
“…Topographic parameters such as elevation and slope can provide indicators of people's access to forests or conversion of forest lands into other uses as farming (plantations) and acquisition for construction [22]. Slope is also a controlling factor in land surface processes because it affects soil properties and water content in addition to the potential for erosion of forest lands located on steep slopes or high altitudes [22,86].…”
Section: Variables Acquisition Related To Drivers Of Change In Forestmentioning
confidence: 99%